(untitled) (Research, Society and Development, 2021)
Extreme air temperatures are changeable over time and regions and have an annual variation in their characteristics, the analysis of short periods, provided that they are carried out for successive years of at least ten years, provide an assessment of the area’s climate behavior. The objective is to evaluate, temporally and spatially, the climatic trends, annual and seasonal, of extreme and average temperature for São Bento do Una - Pernambuco between 1950-2020, as well as to discuss possible causes. It is hoped that this information will be able to subsidize researchers and government authorities in several areas of activity, especially in agriculture and poultry. The extreme and average thermal data were generated by the Estima_T software (1950-2020) and the data was divided every 10 years. Basic statistics were used to calculate the means and other parameters relevant to the development of the study. The data on thermal air buoyancy aids decision-making in the agricultural, urban and rural agribusiness in multiple areas of knowledge. The average temperature is the representation of the variability and its oscillations of the extreme temperatures, any variability in these elements the average temperatures adapt to their oscillations of the synoptic systems acting in the rainy and dry season as well as the impacts on the environment and its elevation in relation sea ​​level. Climatic variability recorded on a global, regional and local scale was found in the studied area, for sixty-seven years of data.